Spymaster [compact disc, unabridged] : a thriller - Thor, Brad (Thor, Brad. Scot Harvath., 2018)
Across Europe, a secret organization has begun attacking diplomats. Back in the United States, a foreign ally demands the identity of a highly placed covert asset. In the balance hang the ingredients for all-out war. With his mentor out of the game, counterterrorism operative Scot Harvath must take on the role he has spent his career avoiding. But, as with everything else he does, he intends to rewrite the rules--all of them. In Spymaster, Scot Harvath is more cunning, more dangerous, and deadlier than ever before.